Effects of Production and Operating Costs on Net Profit on Manufacturing Companies Registered in JII - Arbarija Hafiz Lubis; Sugianto, Sugianto; Kusmilawaty, Kusmilawaty (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This research aims to determine the influence of production costs and operational costs on net profit in manufacturing companies listed on the Jakarta Islamix Index (JII) for the 2018-2022 period by classifying sharia stock index companies that operate in the consumption sector. Quantitative research methods are descriptive and verification approaches that describe a variable based on quantitative data analysis with statistical procedures to test a research data hypothesis. The data analysis technique used is panel data regression analysis. Hypothesis tests used include the T test, F test, and coefficient of determination. And data processing is assisted with the E Views for Windows Version 12.00 device. The samples studied were 7 manufacturing companies at JII in the last 5 years (2018-2022). The research results are based on an analysis of manufacturing companies listed on the Jakarta Islamic Index (JII) in 2018 - 2022. Production costs (X1) partially have no significant negative effect on Net Profit (Y) and operational costs (X2) partially have a significant positive effect on Net Profit (Y). Production costs (X1) and operational costs (X2) simultaneously do not have a significant effect on Net Profit (Y).